The effects of e-procurement practices and risk management on procurement performance through sustainable supply chain - AlQubaisi, Ahmed Jumaa (2024)
In today's dynamic business environment, risk management (RM) plays a vital role in identifying opportunities and threats, guiding decision-making, and shaping the future of organizations. Effective procurement methods remain crucial for success in the oil and gas sector. However, poor procurement performance often leads to delivery delays, growth failures, and distribution challenges. With advancements in technology, organizations are increasingly leveraging electronic procurement (e-procurement) and RM to enhance their supply chains and overall procurement performance. This study focuses on Abu Dhabi National Oil Company (ADNOC), a prominent energy company in the UAE, which has adopted e-procurement to streamline its procurement process. The study aims to investigate the interplay of eprocurement, RM, and sustainable supply chain (SSC) and their impact on procurement effectiveness within ADNOC. A conceptual framework is proposed, and the study examines the correlation between these factors and procurement performance. Data was collected through a random sample of 376 personnel from ADNOC's procurement, evaluation, and management levels. Structural equation modeling (SEM) using AMOS software was employed to analyze the collected data and assess the study hypotheses. The findings revealed a strong positive association between procurement success and e-procurement, RM, and SSC. Additionally, the study identified the mediating role of SSC in the relationship between RM and procurement performance. This research contributes theoretically by validating the dimensions of e-procurement, RM, SSC, and procurement performance through exploratory factor analysis and confirmatory factor analysis. It also establishes the mediating role of SSC in the oil and gas industry. Furthermore, the study provides statistical evidence supporting the proposed framework, which serves as a valuable model for companies relying on procurement for sustained business operations. The findings have practical implications for decision-makers at ADNOC and other oil and gas companies, enabling them to understand the impact of e-procurement, RM, and SSC on procurement success. Moreover, policymakers and stakeholders in the oil industry worldwide can benefit from the insights into the mediating role of SSC. This research contributes to advancing procurement practices and enhancing performance in the oil and gas sector, ensuring sustainable operations in an ever-evolving business landscape.